A DIJKSTRA ALGORITHM IMPLEMENTATION IN DETERMINING SHORTEST ROUTE TO MOSQUE IN RESIDENTIAL CITRA INDAH CITY - Lestari, Siti Lestari; Ardiansyah, Ardiansyah; Giovani, Angelina Puput; Dwijayanti, Desy (Jurnal Pilar Nusa Mandiri, 2020)
The application of artificial intelligence (Artificial Intelligence) for problem-solving in the field of computer science has experienced rapid development from year to year as the development of artificial intelligence itself. Problems involving searching (searching) is one example of the use of artificial intelligence that is quite popular to solve various kinds of problems. In daily activities, the use of roads is always an unavoidable activity, so determining the shortest path from one point to another becomes a problem that is often encountered. This is also felt by residents who live in a large enough housing. Sometimes to be able to reach the destination they are often confused in deciding which way to go to get the shortest distance to the destination. Citra Indah City Housing is a residential area in the Jonggol District area, Bogor Regency, developed by the Ciputra group. Within the Vignolia Hill Cluster, there is a mosque located on the northwest corner of the Vignolia Hill cluster or at the western end of the AH.17 block. A large number of blocks raise problems regarding the shortest route that can be taken by residents to get to the mosque. So, the purpose of this research is to determine the shortest path taken by citizens to get to the mosque. The method used is to apply the Djikstra algorithm which is able to produce the shortest route for residents to get to the mosque.